A new test method for the characterization of the bending behavior of textile prepregs. (June 2017) - Alshahrani, Hassan; Hojjati, Mehdi
Abstract: To improve forming simulation outcomes for composite prepregs and predict wrinkle formation, the bending behavior of prepreg materials must be correctly characterized. This paper proposes a new loading-rate control bending test in which the sample deflection and applied rate are controlled by a linear actuator while the load required to achieve this deflection is recorded by a miniature-load cell. An investigation of out-of-plane bending behavior as well as viscoelastic behavior at the forming process conditions of woven fabric out-of-autoclave prepregs was undertaken using this method. The experimental results show that the proposed bending test provides sufficient control of the deflection shape, testing rates, and processing temperatures within the range of thermosetting resin. Furthermore, the bending results reveal the rate dependency and viscoelastic nature of the materials. A method is developed to derive the bending stiffness from the nonlinear relationship between bending moment and curvature.